Treatment outcome of tuberculosis patients at Gondar University Teaching Hospital, Northwest Ethiopia. A five - year retrospective study - Bekele Assegedech; Muche Abebe; Tessema Belay; Reissig Dieter; Emmrich Frank; Sack Ulrich (BMC, 2009)
Abstract Background In Gondar University Teaching Hospital standardized tuberculosis prevention and control programme, incorporating Directly Observed Treatment, Short Course (DOTS) started in 2000. According to the proposal of World Health Organization (WHO), treatment outcome is an important indicator of tuberculosis control programs. This study investigated the outcome of tuberculosis treatment at Gondar University Teaching Hospital in Northwest Ethiopia. Methods We analyzed the records of 4000 tuberculosis patients registered at Gondar University Teaching Hospital from September 2003 to May 2008. Treatment outcome and tuberculosis type were categorized according to the national tuberculosis control program guideline. Multivariate analysis using logistic regression model was used to analyse the association between treatment outcome and potential predictor variables. Results From the total of 4000 patients, tuberculosis type was categorized as extrapulmonary in 1133 (28.3%), smear negative pulmonary tuberculosis in 2196 (54.9%) and smear positive pulmonary tuberculosis in 671 (16.8%) cases. Of all patients, treatment outcome was classified as successfully treated in 1181(29.5%), defaulted in 730 (18.3%), died in 403 (10.1%), treatment failed in six (0.2%) and transferred out in 1680 (42.0%) patients. Males had the trend to be more likely to experience death or default than females, and the elderly were more likely to die than younger. The proportion of default rate was increased across the years from 97(9.2%) to 228(42.9%). Being female, age group 15-24 years, smear positive pulmonary tuberculosis and being urban resident were associated with higher treatment success rate. Conclusion The treatment success rate of tuberculosis patients was unsatisfactorily low (29.5%). A high proportion of patients died (10.1%) or defaulted (18.3%), which is a serious public health concern that needs to be addressed urgently.